Flammability hazards of typical fuels used in wind turbine nacelle - Wang,Z; You,F; Rein,G; Jiang,J; Han,X; Han,J; Sun,W (Fire and Materials, 2018)
This study aims to develop a complete methodology for assessing flammability hazards of typical fuels (ie, transformer oil, hydraulic oil, gear oil, and lubricating grease) used in a wind turbine nacelle by combining different experimental techniques such as thermogravimetric analysis and cone calorimetry. Pyrolysis properties (onset temperature, temperature of maximum mass loss rate, and mass residue) and reactiontofire properties (ignition time, heat release rate, mass loss rate, and smoke release rate) were determined and used for a preliminary assessment of thermal stability and flammability hazards. Additional indices, for ignition and thermal behavior (effective heat of combustion, average smoke yield, and smoke point height, heat release capacity, fire hazard parameter, and smoke parameter, were calculated to provide a more advanced assessment of the hazards in a wind turbine. Results show that pyrolysis of transformer oil, lubricating grease, hydraulic oil, and gear oil occur in the range of 150°C to 550°C. Lubricating grease and transformer oil show the higher and lower thermal stabilities with maximum pyrolysis rate temperatures of 471°C and 282°C, respectively. The measured relation between ignition time and radiant heat flux agrees well with Janssens method (a power of 0.55). The aforementioned indices appear to provide a reasonable prediction of performance under real fire conditions according to a fullscale fire test documented by Declercq and Van Schevensteen. The results of the study indicate that transformer oil is the easiest to ignite while lubricating grease is the most difficult to ignite but also has the highest smoke production rate; that transformer oil has the highest heat release rate while gear oil has the lowest; and that the fire hazard parameter is the highest for transformer oil and the smoke parameter is the highest for lubricating grease. The potential of this type of work to design safer wind turbines under perfor